Primitive programing algebra: general approfch to a problem of functional completeness - Yahanov, P.O.; Redko, D.I.; Redko, I.V.; Zakharchenko, T.L. (Системні дослідження та інформаційні технології, 2015)
The goal of the research is development of scientific foundations of programming problems solutions genesis. Investigations carried out are based on algebraic research methods of programs and compositional programming methods. Basis of the last ones consists of program algebras with special classes of functions as carriers, and compositions that represent abstractions from program synthesis tools as operations. Problems of completeness in classes of computable functions that took one of the most important places in programming problems are well defined and solved in the context of program algebras. Universal method for the problem of completeness solution in primitive program algebras (PPA) on different classes of computable functions proposed in the article. Results achieved are presented as series of original statements, lemmas and theorems. The results can be applied in algebraic characteristics research of different computable functions classes in problems of programming language semantics formalization.